Structure and Function of p97 and Pex1/6 Type II AAA+ Complexes - Saffert, Paul; Enenkel, Cordula; Wendler, Petra (Frontiers in Molecular Biosciences, 2017)
Protein complexes of the Type II AAA+ (ATPases associated with diverse cellular activities) family are typically hexamers of 80-150 kDa protomers that harbor two AAA+ ATPase domains. They form double ring assemblies flanked by associated domains, which can be N-terminal, intercalated or C-terminal to the ATPase domains. Most prominent members of this family include N-ethyl-maleimide sensitive factor, p97/VCP (valosin-containing protein), the Pex1/Pex6 complex and Hsp104 in eukaryotes and ClpB in bacteria. Tremendous efforts have been undertaken to understand the conformational dynamics of protein remodeling type II AAA+ complexes. A uniform mode of action has not been derived from these works. This review focuses on p97/VCP and the Pex1/6 complex, which both structurally remodel ubiquitinated substrate proteins. P97/VCP plays a role in many processes, including ER- associated protein degradation, and the Pex1/Pex6 complex dislocates and recycles the transport receptor Pex5 from the peroxisomal membrane during peroxisomal protein import. We give an introduction into existing knowledge about the biochemical and cellular activities of the complexes before discussing structural information. We particularly emphasize recent electron microscopy structures of the two AAA+ complexes and summarize their structural differences.